Design and Development of a Web-Based Point of Sale System at Warung Bang Nopi (POLITEKNIK LP3I JAKARTA, 2026)
This research aims to design and develop a web-based Point of Sale (POS) information system to overcome operational challenges at Warung Bang Nopi, a micro, small, and medium enterprise (MSME) in Central Jakarta. The existing manual management leads to inaccurate inventory tracking, lost debt records, unrecorded transaction history, and financial calculation errors. To address these issues, the system was modeled using Unified Modeling Language (UML) with three main actors (Owner, Admin, and Cashier). The software was developed using the Model-View-Controller (MVC) architecture, utilizing the CodeIgniter framework, PHP programming language, and MySQL DBMS. Functional testing using Black-box testing confirmed that all features operate properly. The final result is a POS system that automates store operations, prevents the loss of debt records, and secures real-time financial reporting. Consequently, this system significantly enhances daily operational efficiency and supports strategic decision-making for the business.